Association of height, foot length, and pubertal development in children aged 3–18: a cross-sectional survey in China - Wu, Hua-Hong; Zhang, Ya-Qin; Yu, Cheng-Dong; Yang, Li; Tao, Chen; Shu, Wen; Li, Tao; Huang, Guimin; Hou, Dongqing; Chen, Fang-Fang; Liu, Jun-Ting; Li, Shao-li; et al. (Frontiers in Public Health, 2024)
Objective This study aimed to analyze the growth patterns of height and foot length (FL) among Chinese children aged 3–18 and examine their associations with puberty development. Methods A cross-sectional survey was conducted in September 2022 in Beijing. Data were collected through questionnaires and on-site physical examinations. The growth patterns and velocity of height and FL in different age groups were described, and their associations with puberty development were analyzed. Results From an age perspective, the peak FL growth occurred between 9 and 11 years (boys were 11 years and girls were 9 years), while the peak height growth occurred at 11 ~ 13 years for boys and 9 ~ 11 years for girls. Additionally, boys and girls reached 99.0% of their final FL at the ages of 14 and 13, respectively, while they reached 99.0% of their final height at the ages of 16 and 15, respectively. From the perspective of Tanner stage, the age of peak FL growth in boys coincided with the age of the G2 stage, while in girls it occurred slightly earlier than the mean age of the B2 stage. The peak height growth for both boys and girls occurred between Tanner stages 2 and 3. Conclusion Boys and girls reach their peak FL growth at 11 and 9 years old, respectively, which were both 2 years earlier than their peak height growth. The peak FL growth occurred around the onset of puberty, while the peak height growth occurred between Tanner stages 2 and 3.